Pengaruh Produktivitas Desa Wisata, Stabilisasi Ekonomi dan Knowledge Management Terhadap Keberlanjutan Usaha (Studi Empiris Pada Balkondes Di Borobudur) - Nugraheni, Nur Aisah; Hana, Marisa Tri; Shofiyani, Dianah; Candra, Septian Dwi; Fadhilah, Ilfi Nur; Muhdiyanto (Universitas Muhammadiyah Metro, 2024)
Sustainable tourism development is a business developed using various economic approachescovering various aspects ranging from science, human resource technology, and localbusiness empowerment. In business sustainability, not only certain parties are responsible formaking efforts, but also all elements must be able to contribute to these efforts. This researchaims to analyze the influence of tourist village productivity, economic stabilization andknowledge management on business sustainability at the Balcony Village in Borobudur. Thisresearch uses quantitative methods with the population in the study being Balcondes andBUMDes managers in 20 Balcondes in Borobudur. The sample in this study was 165respondents using a purposive sampling method with a minimum criteria of 6 months ofwork. The analytical tool used is multiple linear regression with processing using SPSS. Theresults of this research show that tourism village productivity, economic stabilization, andknowledge management have a positive effect on business sustainability, supported by theTriple Bottom Line theory to prepare and complement organizational needs in terms of economic, social and environmental aspects, so that they are able to compete and continue tobe sustainable